Whose Lane Is It Anyway? The Experience of Cycling in a Mid-Sized City. (23rd November 2020) - Mayers, Rebecca Fallon; Glover, Troy D.
Abstract: The need to upgrade infrastructure for cycling has never been greater, yet urban development in North America continues to privilege car usage. Cities are responding by encouraging alternate modes of transportation through bike-friendly design and planning, but the politics of approving such initiatives remain contentious, even though evidence reveals bikeable cities are beneficial in a variety of ways. The purpose of this study was to explore cyclists' experiences within a car-centric city. To this end, this study engaged with local cyclists directly to understand how their experiences were influenced by their surroundings. This qualitative analysis is organized around three themes: (1) identity as a cyclist, (2) riding in a car-centric city, and (3) lived experience with "bicycle-friendly" infrastructure. Cyclists' experiences offer direction for further research on the topic of cycling in leisure studies.